A literature review on central bank communication. Issue 4 (23rd September 2014) - T. Hughes, Peter; Kesting, Stefan
Abstract : Purpose: – This paper aims to review the economic literature on central bank communication to address the questions of how economists account for the effects of speech acts and whether and to what extent discourse analysis is applied in their studies. Moreover, whether there may be room for more linguistic approaches to analyse central bank communication is investigated. Design/methodology/approach: – A range of recently published (2004-2013) works in the area of central bank communication are critically scrutinized to highlight the current thinking in this area. The sources are organised into different sections, namely, communication in monetary policy theory; impacts of speech acts; optimizing central bank communication; and linguistic analysis of central bank communication. Findings: – The current literature is developing a coherent argument that central bank communication is an important part of monetary policy and that speech acts by the central bank do have impacts at the macroeconomic level. Linguistic analysis does have the potential to contribute to this literature, as little attention has been paid to the content of the speech acts. Originality/value: – This paper fulfils the need for an up-to-date review of the developing literature on central bank communication. This paper also provides support for linguistic analysis in this area.